Hematoma enlargement characteristics in deep versus lobar intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Sprügel, Maximilian; Röder, Sebastian; Madžar, Dominik; Hagen, Manuel; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Annals of Clinical and Translational Neurology, 2020)
Objective: Hematoma enlargement (HE) is associated with clinical outcomes after supratentorial intracerebral hemorrhage (ICH). This study evaluates whether HE characteristics and association with functional outcome differ in deep versus lobar ICH. Methods: Pooled analysis of individual patient data between January 2006 and December 2015 from a German-wide cohort study (RETRACE, I + II) investigating ICH related to oral anticoagulants (OAC) at 22 participating centers, and from one single-center registry (UKER-ICH) investigating non-OAC-ICH patients. Altogether, 1954 supratentorial ICH patients were eligible for outcome analyses, which were separately conducted or controlled for OAC, that is, vitamin-K-antagonists (VKA, n = 1186) and non-vitamin-K-antagonist-oral-anticoagulants (NOAC, n = 107). Confounding was addressed using propensity score matching, cox regression modeling and multivariate modeling. Main outcomes were occurrence, extent, and timing of HE (>33%/>6 mL) and its association with 3-month functional outcome. Results: Occurrence of HE was not different after deep versus lobar ICH in patients with non-OAC-ICH (39/356 [11.0%] vs. 36/305 [11.8%], P = 0.73), VKA-ICH (249/681 [36.6%] vs. 183/505 [36.2%], P = 0.91), and NOAC-ICH (21/69 [30.4%] vs. 12/38 [31.6%], P = 0.90). HE extent did not differ after non-OAC-ICH (deep:+59% [40–122] vs. lobar:+74% [37–124], P = 0.65), but both patients with VKA-ICH and NOAC-ICH showed greater HE extent after deep ICH [VKA-ICH, deep: +94% [54–199] vs. lobar: +56% [35–116], P < 0.001; NOAC-ICH, deep: +74% [56–123] vs. lobar: +40% [21–49], P = 0.001). Deep compared to lobar ICH patients had higher HE hazard during first 13.5 h after onset (Hazard ratio [HR]: 1.85 [1.03–3.31], P = 0.04), followed by lower hazard (13.5–26.5 h, HR: 0.46 [0.23–0.89], P = 0.02), and equal hazard thereafter (HR: 0.96 [0.56–1.65], P = 0.89). Odds ratio for unfavorable outcome was higher after HE in deep (4.31 [2.71–6.86], P < 0.001) versus lobar ICH (2.82 [1.71–4.66], P < 0.001), and only significant after small-medium (1st volume-quarter, deep: 3.09 [1.52–6.29], P < 0.01; lobar: 3.86 [1.35–11.04], P = 0.01) as opposed to large-sized ICH (4th volume-quarter, deep: 1.09 [0.13–9.20], P = 0.94; lobar: 2.24 [0.72–7.04], P = 0.17). Interpretation: HE occurrence does not differ among deep and lobar ICH. However, compared to lobar ICH, HE after deep ICH is of greater extent in OAC-ICH, occurs earlier and may be of greater clinical relevance. Overall, clinical significance is more apparent after small–medium compared to large-sized bleedings.
CRIS-Team Scopus Importer:2020-03-17